The Impact of Graduates' Skills on Facing Challenges in the Labor Market - Arbëresha Behluli; Fidan Qerimi; Fellanze Pula; Lulzim Shabani (Ital Publication, 2022)
Objectives: This study aims to measure the impact of graduate skills on job challenges in the labor market in Kosovo and also to measure the relationship between graduates' challenges at work and demographic characteristics (age, gender, educational level, and training). Methods: Quantitative methods were used to conduct this research, using a structured questionnaire. The study population was graduate students in the last five years in Kosovo, and the sample included 400 students according to Slovin's formula. Findings: Based on the research results, the acquired skills were inversely proportional to the challenges of the graduates in the labor market. According to the multiple linear regression, it turned out that the students' skills negatively affected their challenges. Also, the T-test and ANOVA showed significant results concerning gender, age, and training. Novelty/improvement: Through this research, higher education institutions receive feedback on what needs more attention to better prepare students to face the job market. Hence, the research will contribute to improving the quality of teaching and reducing the challenges graduates face in the labor market. Doi: 10.28991/ESJ-2022-06-02-014 Full Text: PDF